2017
DOI: 10.1080/09546634.2017.1294727
|View full text |Cite|
|
Sign up to set email alerts
|

Psoriasis patients with psoriasis Area and Severity Index (PASI) 90 response achieve greater health-related quality-of-life improvements than those with PASI 75–89 response: results from two phase 3 studies of secukinumab

Abstract: These results show that PASI 90-100 is a relevant therapeutic goal in moderate to severe psoriasis compared to PASI 75-89 when considering patients' QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 27 publications
8
36
0
Order By: Relevance
“…To our knowledge, all previous research investigating the relationship between HRQoL and skin clearance per PASI percentage responder group is from a clinical trial setting. Several RCTs report higher DLQI improvements in PASI 90<100 patients compared with PASI 75<90 patients . We found no studies reporting DLQI or EQ‐5D response at different levels of PASI percentage response from a clinical practice setting.…”
Section: Discussionmentioning
confidence: 69%
“…To our knowledge, all previous research investigating the relationship between HRQoL and skin clearance per PASI percentage responder group is from a clinical trial setting. Several RCTs report higher DLQI improvements in PASI 90<100 patients compared with PASI 75<90 patients . We found no studies reporting DLQI or EQ‐5D response at different levels of PASI percentage response from a clinical practice setting.…”
Section: Discussionmentioning
confidence: 69%
“…In efficacy evaluation of each drug for psoriasis, the algorithm has been proposed that switching to other drugs should be considered for patients not achieving PASI‐50 or for patients showing improvements corresponding to 50 ≤ PASI < 75 and DLQI scores of more than 5. However, with recent advances in trials for the development of biologics, there is an opinion that PASI‐90 and a DLQI score of 0 or 1 (DLQI remission) should be set as treatment goals rather than PASI‐75 and DLQI scores of ≤5 While biologics available for psoriasis are increasing, switching from a biologic to another biologic, namely bio‐switch, has been frequently performed due to secondary failure (therapeutic effects observed for a certain period subsequently decrease and symptoms worsen during continuous treatment), adverse reactions, patients’ requests or other reasons.…”
Section: Eligible Patients For Treatment With Biologicsmentioning
confidence: 99%
“…However, with recent advances in trials for the development of biologics, there is an opinion that PASI-90 and a DLQI score of 0 or 1 (DLQI remission) should be set as treatment goals rather than PASI-75 and DLQI scores of ≤5. 79 • While biologics available for psoriasis are increasing, switching from a biologic to another biologic, namely bio-switch, has been frequently performed due to secondary failure (therapeutic effects observed for a certain period subsequently decrease and symptoms worsen during continuous treatment), adverse reactions, patients' requests or other reasons. It has been demonstrated that, even in patients previously treated with biologics and in patients responding inadequately to previous biologics, most newly approved biologics can be expected to be effective to a certain extent.…”
Section: Selection Criteria Of Biologicsmentioning
confidence: 99%
“…Meanwhile, Torii et al [42] in their study on infliximab considered that a PASI 90 response is necessary to achieve a treatment goal stated in the European S3 guidelines: a DLQI of 0 or 1 (no effect on patient’s QoL). More recently Elewski et al [43] in a study on secukinumab have shown that psoriatic patients with a PASI 90 response achieve greater health-related QoL improvements than those with a PASI 75–89 response and concluded that PASI 90–100 is a relevant therapeutic goal in moderate-to- severe psoriasis. Abrouk et al [44] found a statistically significant difference in DLQI scores between the patients on adalimumab achieving PASI 75 and the patients achieving PASI 90 at week 24, but not at week 12, and did not find a statistically significant difference in DLQI between the patients on ustekinumab achieving PASI 75 and the patients achieving PASI 90 at week 24.…”
Section: Hrqol Assessment In Dermatological Guidelinesmentioning
confidence: 99%